An effective wavelet method to detect and mitigate low-frequency multipath effects - Souza, E. M. [UNESP]; Monico, J. F G [UNESP]; Polezel, W. G C [UNESP]; Pagamisse, A. [UNESP] (Springer Nature, 2008)
To ensure high accuracy results from GPS relative positioning, the multipath effects have to be mitigated. Although the careful selection of antenna site and the use of especial antennas and receivers can minimize multipath, it cannot always be eliminated and frequently the residual multipath disturbance remains as the major error in GPS results. The high-frequency multipath from large delays can be attenuated by double difference (DD) denoising methods. But the low-frequency multipath from short delays is very difficult to be reduced or modeled. In this paper, it is proposed a method based on wavelet regression (WR), which can effectively detect and reduce the low-frequency multipath. The wavelet technique is firstly applied to decompose the DD residuals into the low-frequency bias and high-frequency noise components. The extracted bias components by WR are then directly applied to the DD observations to correct them from the trend. The remaining terms, largely characterized by the high-frequency measurement noise, are expected to give the best linear unbiased solutions from a least-squares (LS) adjustment. An experiment was carried out using objects placed close to the receiver antenna to cause, mainly, low-frequency multipath. The data were collected for two days to verify the multipath repeatability. The ground truth coordinates were computed with data collected in the absence of the reflector objects. The coordinates and ambiguity solution were compared with and without the multipath mitigation using WR. After mitigating the multipath, ambiguity resolution became more reliable and the coordinates were more accurate.
Keywords: GPS; Low-frequency multipath; wavelets regression; Ambiguity resolution; High frequency measurements; High-frequency noise; Multi-path disturbances; Multi-path mitigation; Multipath; Relative positioning; Antennas; Geodesy; Geodetic satellites; Site selection; Global positioning system